In vivo evaluation of outer retinal function and structure after retrobulbar optic nerve crush by lateral orbitotomy in goats. (August 2021) - Zhang, Yikui; Sun, Jiaying; Ye, Qian; Jiang, Wenhao; Hong, Huifeng; Jiang, Xiaohui; Xia, Yu; Zhang, Si; Wu, Wencan
Abstract: Large animal model of optic nerve crush (ONC) plays an important role in translating novel therapeutic strategies developed in rodent model to clinical application. Due to the poor accessibility of the optic nerve (ON) in humans and large animals, lateral orbitotomy is needed to expose the retrobulbar ON. This study was to explore the effects of ONC and ON exposure with lateral orbitotomy (sham surgery) on the outer retinal function and structure in goats by using standard flash electroretinogram (FERG) and spectral-domain optical coherence tomography (SD-OCT). We found that ONC led to a transient reduction in FERG amplitudes at 1 week post injury (wpi), which recovered gradually over 2 months afterwards. Sham surgery alone also caused a similar pattern of amplitude reduction in FERG, although not as significantly as ONC did. Transient outer retinal thickening following ONC occurred at 4 wpi (when progressive thinning of the ganglion cell complex began), peaked at 8 wpi, then recovered gradually at 12 wpi. In contrast, outer retinal thickness remained unchanged statistically 3 months after sham surgery. Fundus fluorescein angiography showed that neither ONC nor ON exposure with lateral orbitotomy significantly caused any significant delay or absence of central retinal vascular filling. In summary, ONC with lateral orbitotomy affects outer retinal function and structure transiently. Highlights: Outer retinal function and structure were evaluated after retrobulbar optic nerve crush (ONC) in goats. Transient FERG amplitude reduction was observed following ONC. The thickness of outer retina measured by OCT underwent a transient increment following ONC. FFA test revealed that the central retinal vasculature remained normal following ONC.